2013
DOI: 10.2478/tumor-2013-0002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Wee1 inhibition on the hypoxia-induced DNA damage response

Abstract: Tumor hypoxia is a common feature associated with resistance to current anticancer therapies, such as radiotherapy and chemotherapy. Wee1 is a tyrosine kinase regarded as a gatekeeper of the G 2 /M cell cycle transition. Wee1 has recently been highlighted as a therapeutic target in cells with a deficient G 1 checkpoint, since they are more reliant on the G 2 phase for repair of damage and survival. Here, we have assessed the impact of Wee1 inhibition on hypoxic cells and its therapeutic potential as a single a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The metabolic reprogramming associated with CDK4, CDK6, and EGFR is responsible for ROS and is reportedly targeted by abemaciclib and cetuximab [101,102]. Inhibiting genomic stability via targeting ATM by fenofibrate and enhancing cell death by inhibiting CHK1 by WEE1 and kinases-PI3K by alpelisib can decrease radioresistance [103,104].…”
Section: Implications Of Riar On Cancer Radiotherapymentioning
confidence: 99%
“…The metabolic reprogramming associated with CDK4, CDK6, and EGFR is responsible for ROS and is reportedly targeted by abemaciclib and cetuximab [101,102]. Inhibiting genomic stability via targeting ATM by fenofibrate and enhancing cell death by inhibiting CHK1 by WEE1 and kinases-PI3K by alpelisib can decrease radioresistance [103,104].…”
Section: Implications Of Riar On Cancer Radiotherapymentioning
confidence: 99%
“…Of note, a recent report demonstrated decreased viability of hypoxic A549, H1299, and H1975 lung cancer cell lines after treatment with a hypoxia-activated Chk1 inhibitor (the CH-01 prodrug; Cazares-Korner et al, 2013 ), indicating that hypoxic lung tumors may be sensitive to Chk1 inhibitors. In contrast, a single study suggested that hypoxia does not sensitize H1299 lung cancer cells to the Wee1 inhibitor MK1775 ( O’Brien et al, 2013 ).…”
Section: The Potential Of Atr/chk1/wee1 Inhibitors For Treatment Of Lmentioning
confidence: 99%